1991
DOI: 10.1121/1.2029902
|View full text |Cite
|
Sign up to set email alerts
|

The release of air bubbles from an underwater nozzle

Abstract: Air bubbles released from an underwater nozzle emit an acoustical pulse that is of interest both for the study of bubble detachment and for elucidating the mechanism of sound generation by a newly formed bubble. In this paper, the sequence of bubble shapes is calculated theoretically from a given nozzle, and it is shown that there is for each nozzle a bubble of maximum volume Vmax. Assuming that the bubble becomes detached at its “neck,” and that the volume of the detached bubble equals the volume V* of the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
65
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(76 citation statements)
references
References 0 publications
11
65
0
Order By: Relevance
“…Other studies observed bubble growth and shape from appearance in the tip of an orifice or capillary tube until detachment (Kupferberg and Jamenson, 1969;Pinczewski, 1981;Gaddis and Vogelpol, 1986;Tsuge, 1986;Longuet-Higgins et al, 1991;Oguz and Prosperetti, 1993;Teresaka and Tsuge, 1993;Sundar and Tan, 1999;Hé brard, 2003, 2004). However, detailed observations of the bubble formation process from appearance at the capillary tube tip through detachment are lacking in the literature.…”
Section: Introductionmentioning
confidence: 94%
“…Other studies observed bubble growth and shape from appearance in the tip of an orifice or capillary tube until detachment (Kupferberg and Jamenson, 1969;Pinczewski, 1981;Gaddis and Vogelpol, 1986;Tsuge, 1986;Longuet-Higgins et al, 1991;Oguz and Prosperetti, 1993;Teresaka and Tsuge, 1993;Sundar and Tan, 1999;Hé brard, 2003, 2004). However, detailed observations of the bubble formation process from appearance at the capillary tube tip through detachment are lacking in the literature.…”
Section: Introductionmentioning
confidence: 94%
“…In Fig It is worth noting that there is a 2/5 or 1/2 scaling exponent after the 1/3 -scaling as reported in Ref (Lu et al, 2014a;van Hoeve et al, 2011) as demonstrated in Table 1, which is not observed in this study. In addition, the exponent of 1/3 is smaller than 1/2 that was observed for bubble formation in a static low viscosity liquid in a large container without confining boundaries, for which the breakup was predominated by the inertial forces (Burton et al, 2005;Gekle et al, 2009;Longuet-Higgins et al, 1991;Thoroddsen et al, 2007). …”
Section: Scaling Law For the Evolution Of The Minimum Diameter Of Thementioning
confidence: 91%
“…The Rayleigh-Plesset equation can not predict the break-up because it assumes that expansion is confined in the radial direction homogenously. As a result, the details of flow physics and development can not be captured, and this bubble model is more suitable for a low-speed jet [14,15]. For a high-speed jet, the Navier-Stokes equation is a better candidate to numerically assess the flow structures.…”
Section: Introductionmentioning
confidence: 97%